Haptic Perception, Mechanics, and Material Technologies for Virtual Reality. (11th February 2021) - Biswas, Shantonu; Visell, Yon
Abstract: Emerging virtual and augmented reality technologies can transform human activities in myriad domains, lending tangible, embodied form to digital data, services, and information. Haptic technologies will play a critical role in enabling human to touch and interact with the contents of these virtual environments. The immense variety of skilled manual tasks that humans perform in real environments are only possible through the coordination of touch sensation, perception, and movement that together comprise the haptic modality. Consequently, many research groups are vigorously investigating haptic technologies for virtual reality. A longstanding research goal in this area has been to create haptic interfaces that allow their users to touch and feel plausibly realistic virtual objects. In this progress report, the perspective on this unresolved research challenge is shared, guided by the observation that no technologies can even approximately match the capabilities of the human sense of touch. Factors that have it challenging to engineer haptic technologies for virtual reality, including the extraordinary spatial and temporal tactile acuity of the skin, and the complex interplay between continuum mechanics, haptic perception, and interaction are identified. The perspective on how these challenges may be overcome through convergent research on haptic perception, mechanics, electronics, and material technologies is presented. Abstract : Emerging haptic technologies for virtual and augmented reality hold the potential to transform human activities in myriad domains. This progress report describes research challenges that arise in engineering haptic devices, including performance requirements arising from human abilities. It describes how these challenges may be met through convergent research on perception, mechanics, electronics, and functional material technologies.